One-pot surface modification of magnetic nanoparticles using phase-transitioned lysozyme for robust immobilization of enzymes. (8th June 2021) - Li, Ling; Gao, Zixi; Zhang, Huige; Du, Hongying; Ren, Cuiling; Qi, Shengda; Chen, Hongli
Abstract : Enzymes were one-pot immobilized between Fe3 O4 nanoparticles and a phase-transitioned lysozyme film, providing a new strategy for enzyme immobilization. Abstract : As free enzymes are often limited due to the poor operational stability, high cost and no reusability, immobilization of enzymes is a preferred way to overcome the obstacles. Herein, a 2D protein self-assembly film was first reported to capture functional enzymes without any further chemical modification. Enzymes are immobilized between Fe3 O4 nanoparticles and the robust phase-transitioned lysozyme film, which prevented the leaching of enzymes and ensured the contact of enzymes and substrates. The immobilized enzyme was characterized by FT-IR, TEM, TGA and VSM analysis. Furthermore, the pH stability, thermal stability, storage stability and reusability were greatly improved after the immobilization of the enzyme. Our work provides a nontoxic and inexpensive strategy for enzyme immobilization, which has promising potential in inhibitor screening and enzyme engineering.